Penalaran Berbasis Kasus Untuk Menentukan Pajak Bumi Dan Bangunan - Abdul Rozaq; Latjuba Sofyana (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Calculating land and building taxes requires a measure of land area and estimated costs when building a house. As such, tools are needed that can predict building material requirements appropriately and quickly. The CBR approach can be used to solve these problems, where the method is able to reason to solve problems based on existing cases as a solution to new problems. The system built in this study is a CBR system to determine the building material needs of a house. The consultation process is carried out by entering a new problem compared to the old case then the similarity value is calculated using the nearest neighbor. calculation with data on land area of 100 meter2, building area of 38 meter2, quality of type 2 building, 2 bedrooms, 1 bathroom, lightweight steel roof truss and cast tile, then the accuracy value is 0.985 of type 38 from base case so that there is an earth tax and buildings amounting to Rp. 100,389.4. The test results of 111 data test cases, obtained 9 cases that have similarity values below 0.8